Self-propelled ferroptosis nanoinducer for enhanced cancer therapy - Wenxin Xu; Hao Tian; Yanzhen Song; Hanfeng Qin; Junbin Gao; Yichi Chen; Weichang Huang; Lin Lin; Haixin Tan; Yicheng Ye; Xiaoting Zhang; Daniela A Wilson; et al. (International Journal of Extreme Manufacturing)
Ferroptosis is a newly proposed type of programmed cell death, which has been associated with a variety of diseases including tumors. Researchers have thereby presented nanoplatforms to mediate ferroptosis for anti-cancer therapy. However, the development of ferroptosis-based nanotherapeutics is generally hindered by the limited penetration depth in tumors, poor active pharmaceutical ingredient (API) loading content and the systemic toxicity. Herein, self-propelled ferroptosis nanoinducers composed of two endogenous proteins, glucose oxidase and ferritin, are presented to show enhanced tumor inhibition via ferroptosis while maintaining high API and biocompatibility. The accumulation of our proteomotors at tumor regions is facilitated by the active tumor-targeting effect of ferritin. The enhanced diffusion of proteomotors is then actuated by efficiently decomposing glucose into gluconic acid and H _2 O _2 , leading to deeper penetration and enhanced uptake into tumors. Under the synergistic effect of glucose oxidase and ferritin, the equilibrium between reactive oxygen species and GSH is damaged, leading to lipid peroxidation. As a result, by inducing ferroptosis, our self-propelled ferroptosis nanoinducers exhibit enhanced tumor inhibitory effects. This work paves a way for the construction of a biocompatible anticancer platform with enhanced diffusion utilizing only two endogenous proteins, centered around the concept of ferroptosis.